2012
DOI: 10.1016/j.jaci.2011.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Asthma in Head Start children: Effects of the Breathmobile program and family communication on asthma outcomes

Abstract: Background Asthma morbidity and mortality rates are high among young inner-city children. Lack of routine primary care provider (PCP) visits, poor access to care, and poor patient-physician communication may be contributing factors. Objective This study evaluated the effects of providing Breathmobile services only, a Facilitated Asthma Communication Intervention (FACI) only, or both Breathmobile+FACI on asthma outcomes, relative to standard care. Methods Children with asthma (n=322, mean age=4 years, 53% m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 34 publications
(34 reference statements)
0
15
0
Order By: Relevance
“…A large trial in asthmatic adults showed no benefits of problem-solving education, and the authors suggested that patients' lack of motivation to achieve high adherence was the main reason for this failure [25]. Similarly, an asthma outreach program in inner-city children with asthma in the USA was of limited benefit when parents lacked the motivation to participate [26]. Apparently these maintaining factors represent determinants of self-management that are difficult to modify, supporting our analysis about the role of such underlying factors in the persistence of modifiable barriers.…”
Section: Discussionmentioning
confidence: 99%
“…A large trial in asthmatic adults showed no benefits of problem-solving education, and the authors suggested that patients' lack of motivation to achieve high adherence was the main reason for this failure [25]. Similarly, an asthma outreach program in inner-city children with asthma in the USA was of limited benefit when parents lacked the motivation to participate [26]. Apparently these maintaining factors represent determinants of self-management that are difficult to modify, supporting our analysis about the role of such underlying factors in the persistence of modifiable barriers.…”
Section: Discussionmentioning
confidence: 99%
“…The data for this study came from 160 families randomized to the PC intervention arm of a clinical trial (described below) which aimed to reduce barriers to accessing healthcare and provide additional support to caregivers in an effort to improve PC clinic attendance among preschool children with asthma enrolled in an urban Head Start system [27]. Children aged 2 to 6 years were screened using a caregiver questionnaire distributed through 66 Head Start sites in Baltimore.…”
Section: Methodsmentioning
confidence: 99%
“…Families interested in participating were mailed a consent form and asked to return a signed copy to the research team. In total, 429 children were deemed eligible, 336 (78%) were consented, and 322 (96%) were randomized to one of the four conditions, of which 160 (50%) were placed in the PC intervention arm [27]. For the purposes of this study, the sample was restricted to African-American caregivers receiving public assistance which represents a population with the highest pediatric asthma morbidity [28].…”
Section: Methodsmentioning
confidence: 99%
“…Delivering the intervention by phone allowed anonymity, was time and cost-efficient for the patient,(41) and circumvented families reluctance for home and office visits for education. (16, 42, 43) Rather than delivering a prescribed curriculum, the peer-trainer’s focus was on meeting parental treatment goals, developing their skills and confidence to provide effective asthma management, and addressing their specific practical and psychological barriers to asthma management. (44) The longitudinal and non-hierarchical nature of the peer-trainer-parent relationship allowed sharing of information and experiences about social and other factors that can undermine effective asthma care.…”
Section: Discussionmentioning
confidence: 99%
“…This friendly, empathetic relationship has been noted in other peer-coaching studies,(24, 39) and may explain the lower attrition rate seen here compared to interventions with similar goals delivered by medically trained personnel. (16, 26, 45, 46) Importantly, program quality was maintained by providing call review and ongoing support for the peer-trainers. (26)…”
Section: Discussionmentioning
confidence: 99%